Tales of conversion in the British press: the body and soul paradigm. (2nd January 2019) - Pennarola, Cristina
ABSTRACT: The present study sets out to investigate religious narratives of conversion in the British press with a view to exploring the public dimension of religion and the general attitudes to religious behaviours and beliefs shaped by popular media. To this end, a small-scale sample of 61 news articles published between 2016 and 2017 in two quality papers, The Guardian and The Telegraph, and two tabloids, The Daily Mail and The Sun, was collected. The analysis has focused on narrative construction, i.e. who is converted, by whom and why, where and when, as well as rhetorical encoding, i.e. voicing, modality, transitivity and lexical sets. Findings show that representation of Muslims in the media is largely based on the upholding of 'negative values', e.g. traditionalism and women's submissive role, while news reports on Christian conversions are supportive of a 'flock' of helpless refugees. Conversions to Christianity and to Islam are both consistently associated with material benefits though of a very different nature: food, clothing, housing, asylum and healthcare for Christians; protection, power and sexual gratification for Muslims. References to the spiritual aspects are in both religions downplayed, suggesting a secular paradigm. Abbreviation: CDA